2009
DOI: 10.1063/1.3152432
|View full text |Cite
|
Sign up to set email alerts
|

Composition dependence of glass transition temperature and fragility. II. A topological model of alkali borate liquids

Abstract: Glass transition temperature and fragility are two important properties derived from the temperature dependence of the shear viscosity of glass-forming melts. While direct calculation of these properties from atomistic simulations is currently infeasible, we have developed a new topological modeling approach that enables accurate prediction of the scaling of both glass transition temperature and fragility with composition. A key feature of our approach is the incorporation of temperature-dependent constraints … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
286
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(300 citation statements)
references
References 83 publications
13
286
1
Order By: Relevance
“…It has been shown that T g is an accurate measure of network connectivity [59][60][61] and follows very precisely any coordination change induced by chemical alloying. This is not only true for chalcogenides but also for binary oxides such as alkali germanate or borate glasses for which a maximum in T g is obtained when the population of some higher-coordinated species maximizes with modifier content 31,55,62 . Ultimately, it is seen that the change from a negative to a positive correlation is strongly tied to the minimum found for the fragility index M (Fig.…”
Section: Competing Effectsmentioning
confidence: 99%
“…It has been shown that T g is an accurate measure of network connectivity [59][60][61] and follows very precisely any coordination change induced by chemical alloying. This is not only true for chalcogenides but also for binary oxides such as alkali germanate or borate glasses for which a maximum in T g is obtained when the population of some higher-coordinated species maximizes with modifier content 31,55,62 . Ultimately, it is seen that the change from a negative to a positive correlation is strongly tied to the minimum found for the fragility index M (Fig.…”
Section: Competing Effectsmentioning
confidence: 99%
“…8, full precision trend given in Fig. 8 caption, see also Melt fragility measures the degree of deviation from Arrhenian behavior of the liquid viscosity, and has been directly related to the temperature dependence of the number of degrees of freedom per atom [61][62][63]. Hence the observed temperature dependence of the coordination numbers is expected to contribute to an increased liquid fragility, as well as to the large thermal expansion coefficient (see Table III and Fig.…”
Section: Temperature Dependence Of the Liquid Structurementioning
confidence: 99%
“…When n > 3, the network is "stressed rigid" due to its high connectivity, whereas the isostatic state is achieved for n = 3. The theory has later been extended by Gupta and Mauro to account for the temperature dependence of the constraints Mauro et al, 2009), allowing for a distinction of the individual constraints based on their chemistry via the constraint onset temperature. Here, we derive a topological hardness model for sodium boroaluminosilicate glasses and validate it against experimental measurements for three distinct series of glasses.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we attempt to apply the hardness model of Smedskjaer et al (2010a) based on topological constraint theory Mauro et al, 2009;Smedskjaer et al, 2010b;Micoulaut, 2011, 2013;Jiang et al, 2013;Rodrigues and Wondraczek, 2013) to predict the composition dependence of sodium boroaluminosilicate glass hardness. The model has been found to be quantitatively predictive for borate glasses (Smedskjaer et al, 2010a,c), borosilicate glasses (Smedskjaer et al, 2011), phosphosilicate glasses (Zeng et al, 2014), and calcium silicate hydrates (Bauchy et al, 2014), but has not yet been tested for a system with three network-forming oxides.…”
Section: Introductionmentioning
confidence: 99%